Breast cancer related lymphedema - Haen, R (2012)
Improvements in the treatment of breast cancer have resulted in better survival rates and less breast cancer related morbidity. Nevertheless, a significant group of patients still experience a diminished quality of life as a result of lymphedema. In the early, often reversible, stage of lymphedema patients can experience subjective changes in the affected area. However, with the traditionally available tools the lymphedema often remains clinically undetectable and patients are denied essential care that can prevent worsening. Furthermore, most lymphedema assessment tools fail to support a clear unambiguous definition of lymphedema. This underlines the need for a sensitive objective measurement method that can assess lymphedema in a subclinical stage. In this study we demonstrated that measuring tissue dielectric constant (TDC) using the MoistureMeter-D is an effective method to detect tissue water changes and could potentially provide a cost-effective adequate tool to measure the early onset of breast cancer related lymphedema (BCRL). Secondarily, we established the correlation between the novel TDC method and the frequently used arm volume measurements and self-assessment questionnaires. A group of 20 female patients with clinically BCRL were included. TDC measurements in both arms and all quadrant of both breast were recorded along with volumetric measurements of both arms. All patients were asked to complete a self-report questionnaire. The novel TDC method detected significantly higher tissue water levels in the affected arm and breast compared to the control side. The TDC ratio between control and affected side showed significant correlation with self-reported pain and discomfort in both arm and breast. In the arm, the TDC method also showed correlation with the volume measurement method. The TDC value of the arm was correlated to age, but not to BMI. This study demonstrates that measuring TDC using the MMD is an effective method for quantifying lymphedema in arm and breast and is an important tool in detecting early TWC changes.